Analisis Kebiasaan Sarapan Pada Remaja di SMK Negeri 3 Bogor - Agnes Savira; Nur Riska; Guspri Devi Artanti (Garina, 2024)
This research aims to analyze the breakfast habits of teenagers at SMK Negeri 3 Bogor. The impact of skipping breakfast is that it causes weight gain, increasing the risk of disease. The recommended breakfast time is 7 or 8 in the morning because they have enough time for breakfast. According to most students, breakfast is a healthy lifestyle and affects their concentration and enthusiasm for studying at school and so that students have a strong immune system. The data collection technique in this research is by distributing a questionnaire which is distributed via the Google Form application which contains 16 statements that have passed validation tests and reliability tests. Other data collection was carried out by reading literature books, the internet, and articles related to the problem topic. The number of respondents in this study was 188 people, 46 men with a percentage of 24.5% and 142 women with a percentage of 75.5%. The indicators contained in the questionnaire include the benefits of breakfast, the impact of breakfast, the time of breakfast, the variety of breakfast, the type of breakfast consumed, and the amount of breakfast. Based on the results of this research, it can be concluded that many factors influence the breakfast habits of teenagers at SMK Negeri 3 Bogor.